Investigation of cell morphology by the TRUImagE digital holographic microscopy system - Chee, Oi Choo (2013)
We report the development of the Three-dimensional Real-time Uninvasive Imaging and Evaluation (TRUImagE) system based on digital holographic microscopy to study the morphological changes in cells undergoing photodynamic therapyinduced cell death. The optical system, based on the Michelson interferometer and configured in transmission mode, and the sample holder incorporating a stage incubator have been developed for monitoring various tumorigenic cell samples without the use of markers. Off-axis digital holograms were recorded with a CCD sensor and numerically reconstructed to provide quantitative phase imaging and 3D morphology of the cells in real time. The system was used to continuously monitor and study, at different time points, the changes in cells after incubation with the photosensitizer followed by activation by the appropriate light dose. Results obtained from the TRUImagE system and biochemical assays will be given.